The role of the hospital in a changing environment. - McKee, M. (World Health Organization, 2000)
Hospitals pose many challenges to those undertaking reform of health care systems. This paper examines the evolving role of the hospital within the health care system in industrialized countries and explores the evidence on which policy-makers might base their decisions. It begins by tracing the evolving concept of the hospital, concluding that hospitals must continue to evolve in response to factors such as changing health care needs and emerging technologies. The size and distribution of hospitals are matters for ongoing debate. This paper concludes that evidence in favour of concentrating hospital facilities, whether as a means of enhancing effectiveness or efficiency, is less robust than is often assumed. Noting that care provided in hospitals is often less than satisfactory, this paper summarizes the evidence underlying three reform strategies: (i) behavioural interventions such as quality assurance programmes; (ii) changing organizational culture; and (iii) the use of financial incentives. Isolated behavioural interventions have a limited impact, but are more effective when combined. Financial incentives are blunt instruments that must be monitored. Organizational culture, which has previously received relatively little attention, appears to be an important determinant of quality of care and is threatened by ill-considered policies intended to 're-engineer' hospital services. Overall, evidence on the effectiveness of policies relating to hospitals is limited and this paper indicates where such evidence can be found.